(untitled) (Psychology Travelogs, 2024)
The article analyzes the features of the emergence and overcoming of the crisis of emotional indifference between marriage partners. It is clarified that the concept of «emotional indifference between marriage partners» reflects a long-term lack of satisfaction from partnership as a result of unfulfillment of mutual expectations and violation of certain norms in the relationship of marriage partners. Signs of emotional indifference are identified (disappearance of romantic moods, appearance of intimate and sexual indifference, disappointment with a partner and inability to establish constructive marital relations, frequent quarrels and conflicts). It was found that spouses do not know effective behavior patterns to overcome the crisis of emotional indifference, members of a married couple consciously or unconsciously tend to assign responsibility for their married life to their partner, do not look for the cause of family disharmony in themselves and do not take responsibility for themselves. It was found that in order to successfully overcome the crisis of emotional indifference, it is important for spouses to know about this problem, to understand the signs, causes and consequences of emotional indifference, to be aware of the type of behavior when emotional indifference appears (aggression, joylessness, avoidance of emotional and intimate intimacy). This will help spouses accept their responsibility for the future of the family union, identify personal resources for solving problems related to emotional indifference, and agree on family responsibilities and expected behavior patterns that contribute to harmonious family relationships. The prospects for further scientific development of approaches are to study the peculiarities of the formation of psychological readiness of spouses to prevent and overcome the crisis of emotional indifference.